An ergonomic assessment of musculoskeletal disorders among airport bag handlers: A case study in Malaysia - Ganesan V.; Saudi A.S.M.; Balakrishnan A.; Shafii N.Z.; Kamarudin M.K.A.; Khairuddin M.Z.F.; Amin N.A.; Abu I.F.; Ridzuan I.S.D. (J. K. Welfare and Pharmascope Foundation, 2024)
Flight baggage handlers are highly exposed to risk factors associated with musculoskeletal disorders. It is a grave issue that needs to be highlighted since the aviation industry in Malaysia is continuously growing to support ongoing demand. Hence it is imperative to have an efficient working practice to smooth the entire airline operation. This study aimed to i) identify an association between heavy lifting with musculoskeletal disorders among flight baggage handlers; and ii) determine the association between age with lower back pain prevalence among flight baggage handlers. The data were collected using the Nordic Musculoskeletal Questionnaire (NMQ), daily observation and informal interviews. Findings of this study demonstrated that the majority of bag handlers in the study area suffer from musculoskeletal disorder (MSD) problem caused by their daily routine work. The most affected body parts of these workers are lower back, upper arm and shoulder whereby more than 60% of the workers have reported suffering from MSD symptoms in these body parts. It is evident from this study that the prevalence of MSDs among airport baggage handlers is high. Thus an effective MSD prevention is highly essential. Prevention of MSD in the workplace requires a strong commitment between the employer and employees within an organisation. The employer is fully responsible in providing a safe workplace, a sound ergonomic principle and proper training on health and safety for all employees. 2018 Pharmascope Publications. All rights reserved.